DEIKSIS DALAM NOVEL HATI SUHITA KARYA KHILMA ANIS: KAJIAN PRAGMATIK - Widya LestarI; I Nyoman Sudika; Wika Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify and describe the types and meanings of deixis found inthe novel Hati Suhita by Khilma Anis. It employs a qualitative approach, focusingon utterances in the novel that contain deictic elements. The data were collectedusing an observational method with a non-participatory technique, combined withnote-taking and literature study through reading and analyzing relevant sources.The data analysis was carried out using both intralingual and extralingual matchingmethods, based on Levinson’s theory of deixis, and the findings are presenteddescriptively in an informal manner. The results reveal the presence of five typesof deixis in the novel: personal deixis, temporal deixis, spatial deixis, discoursedeixis, and social deixis. Each type of deixis carries contextual meanings thatreflect cultural values, social relati ons, and character dynamics within the story.These findings indicate that deixis serves not only a referential function but alsoacts as a marker of social and emotional relationships between characters.